Analisis Surat-Surat RA. Kartini Atas Pemikiran Pendidikan Perempuan dan Relevansinya dengan Pendidikan Islam dalam Keluarga - Nurochman, Nurochman; Ali, Mudzakkir (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2023)
The purpose of this research is, firstly, to find out how the education of indigenous women RA. Kartini. Second, to find out the relevance of RA Kartini's indigenous women's educational thinking to Islamic Education. In this study using the library research method (Library Research) with the main source being a collection of letters "After Darkness, Emergence of Light" translation by Armijn Pane, published by Balai Pustaka in 1938 with 204 pages thick. The primary data in this study is data in the form of quotations of words, phrases, sentences in the collection of letters of R.A. Kartini "After Dark Comes Light" translation by Armijn Pane. Based on the results of the study, it can be concluded that through an analysis of RA Kartini's letters sent to her friends in the Netherlands, at least you will find important parts of RA Kartini's thoughts on indigenous women's education, criticism of socio-culture, anxiety in understanding religion, and her multi-roles. as a daughter, as a wife as well as a mother, and her involvement in the public sphere both in the humanitarian, educational and political realms.